Cloning, expression, and characterization of a membrane progestin receptor and evidence it is an intermediary in meiotic maturation of fish oocytes - Zhu, Yong; Rice, Charles D.; Pang, Yefei; Pace, Margaret; Thomas, Peter (East Carolina University, 2003)
The structures of membrane receptors mediating rapid, nongenomic actions of steroids have not been identified. We describe the cloning of a cDNA from spotted seatrout ovaries encoding a protein that satisfies the following seven criteria for its designation as a steroid membrane receptor: plausible structure, tissue specificity, cellular distribution, steroid binding, signal transduction, hormonal regulation, and biological relevance. For plausible structure, computer modeling predicts that the protein has seven transmembrane domains, typical of G protein-coupled receptors. The mRNA (4.0 kb) is only detected in the brain and reproductive tissues on Northern blots. Antisera only detect the protein (40 kDa) in plasma membranes of reproductive tissues. The recombinant protein produced in an Escherichia coli expression system has a high affinity (Kd 30 nM), saturable, displaceable, single binding site specific for progestins. Progestins alter signal transduction pathways, activating mitogenactivated protein kinase and inhibiting adenylyl cyclase, in a transfected mammalian cell line. Inhibition of adenylyl cyclase is pertussis toxin sensitive, suggesting the receptor may be coupled to an inhibitoryGprotein. Progestins and gonadotropin up-regulate bothmRNA and protein levels in seatrout ovaries. Changes in receptor abundance in response to hormones and at various stages of oocyte development, its probable coupling to an inhibitory G protein and inhibition of progestin induction of oocyte maturation upon microinjection of antisense oligonucleotides are consistent with the identity of the receptor as an intermediary in oocyte maturation. These characteristics suggest the fish protein is a membrane progestin receptor mediating a ‘‘nonclassical’’ action of progestins to induce oocyte maturation in fish. Originally published Proceedings of the National Academy of Sciences, Vol. 100, No. 5, Mar 2003
Keywords: Membrane receptors; Progestin; Oocyte maturation